REVIEW OF MODERN APPROACHES TO MATERIAL STRENGTH ASSESSMENT - DATSIUK, DMYTRO; KUPCHUK, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Material strength criteria are fundamental to understanding the durability and failure limits of materials under various stresses and loading conditions. Different models help predict material behavior under complex conditions, including uniaxial, biaxial, and multiaxial stresses. Among the widely used criteria, the von Mises criterion is essential in predicting yielding in ductile materials, suggesting that yielding occurs when the second deviatoric stress invariant reaches a critical value. The Pisarenko–Lebedev criterion expands on this, accounting for hydrostatic stresses, which is especially useful in brittle materials. The Willam–Warnke criterion is widely applied to concrete and similar materials to predict behavior under triaxial states of stress. The Drucker–Prager criterion generalizes the Mohr-Coulomb model by incorporating a continuous yield surface, making it particularly applicable for soils and other pressure-sensitive materials. Bazant’s theory contributes to understanding concrete's behavior, especially regarding cracking and creep in quasi-brittle materials, a valuable extension to other yield criteria In composites, criteria such as Tsai–Hill, Tsai–Wu, Hashin, and LaRC (LaRC being NASA's laminate analysis criterion) allow for precise predictions of material failure under combined stress states, taking anisotropy and unique composite material responses into account. Hoffman’s criterion further modifies Hill’s theory, addressing the need for additional precision in anisotropic materials Additionally, the Kunze and Goldenblat–Kopnov criteria contribute to the realm of composite materials by providing criteria for different types of failure modes under multi-axial loads, vital for high-performance applications. The Norris criterion also emphasizes composite failure but is particularly useful for cases with complex stress states. Lastly, Puck’s criterion is specialized for fiber-reinforced composites, where failure due to inter-fiber stresses is critical. Overall, these criteria facilitate the assessment of material strength in engineering applications by offering diverse models for various material classes, stress conditions, and practical engineering scenarios.
Keywords: structure; material; strength criterion; stress; strain